Optimal use of immunomodulator and biological therapy in Inflammatory Bowel Disease - TIGHE, DONAL (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2017)
﻿Loss of response (LOR) to anti-TNFa therapy is a significant problem, and leads to increased hospitalisation rates, surgical intervention, and steroid dependency. Loss of response is multifactorial. However there is an increasing awareness that immunogenicity has a significant role to play in this process. Immunogenicity against anti-TNFa leads to antibody formation. Antibodies against anti-TNFa lead to faster drug clearance, as well as blocking drug activity. This culminates in a reduction in anti-TNFa trough levels and loss of response. Therapeutic drug monitoring (TDM) allows anti-TNFa trough and antibody levels, to be measured and doses adjusted or treatment switched, to help overcome loss of response and improve outcomes. This thesis aimed to explore the impact of loss of response to anti-TNFa, and accurately identify predictors of loss of response. In addition to investigate the role of therapeutic drug monitoring, in assessing and overcoming loss of response. The main laboratory aspect of this thesis concerned the use of ELISA techniques, to accurately measure anti-TNFa trough and antibody levels. In brief a sandwich ELISA technique was used to detect anti-TNFa trough (infliximab & adalimumab) and antibody levels. ELISA microplates were coated with human TNFa. Horse radish peroxidise conjugated goat anti-human IgG Fc fragment antibody was added to serum samples, followed by diluted antibody. Substrate Solution tetramethylbenzidine (TMB) was added to each well, followed by the addition of stop solution. Drug concentrations in serum samples were determined using a standard curve generated from absorbance readings of infliximab or adalimumab. One arm of this thesis looked at a retrospective cohort study, which confirmed the impact of loss of response to anti-TNFa therapy, with an overall LOR rate of 42.5% for a cohort on maintenance treatment one year after commencing therapy. In addition this iv retrospective cohort study identified a number of key predictors of LOR, such as smoking, prior anti-TNFa therapy, as well as the protective benefits of combination therapy. Furthermore the link with biochemical response was confirmed, with a CRP <5 mg/L at the end of induction therapy being a significant predictor of clinical response. The potential and usefulness of TDM was also explored in further detail. A retrospective study looked at the role of role of measuring anti-TNFa trough and antibody levels in a stand-alone fashion. Analysis did not identify a relationship, but there was evidence that patients with low trough levels, and loss of response, had higher biochemical markers of disease activity. Therefore further work was undertaken to establish a role for TDM at the key time-points of end of induction therapy, and during an assessment for secondary loss of response. A prospective study looked at the role of TDM during induction therapy. There was a clear link between higher anti-TNFa trough levels at the end of induction with clinical response rates. For infliximab, mean trough levels in responders were 16.4 μg/ml versus 5.3 μg/ml for non-responders (p value = 0.026). Similarly there was a link between higher adalimumab levels and clinical response, though not statistically significant. Secondary LOR to anti-TNFa therapy is multifactorial. TDM helps explore an immune basis behind it. A prospective study utilised TDM with dose intensification, introduction of immunomodulators or a switch in therapy resulting in improved response rates. This is part of an evolving therapeutic strategy to overcome LOR, in a patient focused clinically guided fashion. In conclusion TDM has an increasingly important role in the optimal, patient centred management of IBD.
APPROVED
Keywords: Inflammatory Bowel Disease